Proceedings of the 8th World Congress on Conservation Agriculture - Basch, G. (2022)
Under the banner: The Future of Farming – Profitable and Sustainable Farming with Conservation Agriculture, the 8WCCA highlighted the global contribution of Conservation Agriculture towards achieving these outcomes. It also explored how CA land use can help to address humankind’s major global challenges of climate change, environmental degradation and food security while safeguarding the livelihoods of small and large-scale farmers. The proven benefits of CA in terms of erosion control, carbon sequestration, biodiversity regeneration, and improved water and nutrient cycling are all contributing to the achievement of the manifold objectives of the international conventions and agreements including the Sustainable Development Goals, European Green Deal and F2F Strategy.